Релігійна політика Септимія Севера та культ імператора - Петречко, О. М. (Давнина. Харківський історико-археологічний щорічник, 2016)
Summary O. Petrechko. The Religious Policy of Septimius Severus and Imperial Cult Despite some significant changes in the religious policy, in whole, Septimius Severus was true to religious traditions of the Roman state. Development of an imperial cult continued according to the principles, which were put in place and developed by emperors of previous dynasties. At the same time, there were amplified tendency of granting of divine honors not only to the deceased and officially deified emperors, but also to the living one. While it is up for discussion whether Septimius Severus was truly perceived as a god by his contemporaries, but it is necessary to recognize that he was worshipped as a god and he was esteemed as a god. Thus, Principate of Septimius Severus became the next step in the process of transformation from princeps into dominus, and the veiled monarchy into a barefaced monarchy. Key words: Roman Empire, Principate, Septimius Severus, imperial cult.